American exceptionalism and human rights - Ignatieff, Michael (Princeton University Press, 2005)
With the 2003 invasion and subsequent occupation of Iraq, the most controversial question in world politics fast became whether the United States stands within the order of international law or outside it. Does America still play by the rules it helped create? American Exceptionalism and Human Rights addresses this question as it applies to U.S. behavior in relation to international human rights.